STRATEGIC MANAGEMENT OF MUHAMMADIYAH 12 PAMULANG ELEMENTARY SCHOOL IN IMPROVING SERVICE QUALITY AND EDUCATION GRADUATES - Anis Fauzi; Mochamad Mizzudin; Nana Suryapermana; Ani Lestari (Universitas Ahmad Dahlan, 2021)
Strategic management offers the school to plan a superior strategy to achieve the school's vision and mission. However, in reality, not all schools implement strategic management. So there is a gap between expectations and reality. This study aims to describe the strategic management of SD Muhammadiyah in improving service quality and graduate education. This research is a qualitative study, by taking the object of research in SD Muhammadiyah 12 Pamulang related to superior strategies undertaken by SD Muhammadiyah in improving the quality of services and education graduates. Data collection techniques carried out by observation, interviews, and documentation. Data analysis performed using descriptive methods. The results showed that the strategic management process of SD Muhammadiyah 12 Pamulang in improving service quality and education graduates began with planning through internal and external environmental analysis and the selection, implementation, and evaluation of exemplary strategy implementation